Inline contactless optical measuring of glass fiber properties and retrofitting an adaptive cooling system for glass fiber production - DOĞAN, BARIŞ; ERYILMAZ, OĞUZ (My University, 2022)
Various reinforcing materials are used for fiber-reinforced plastics or composites, e.g. glass fibers, carbon fibers or natural fibers. In terms of volume, glass fiber reinforced plastics (GRP) dominate the composites market with a share of approx. 95% of the total market volume [1]. Glass fibers, along with carbon fibers, are thus the most important fibers in the global economic market. In conventional glass fiber production, the individual filaments are cooled as quickly as possible after leaving the bushing to prevent crystallization of the glass and thus achieve high tensile strength. In more modern plants, cooling fins are often used for this purpose. These are brought as close as possible to the heated bushing (approx. 1250 °C) to cool the exiting glass as quickly and efficiently as possible. The flow rate of the coolant is usually only adjusted manually and not actively controlled. As a result, homogeneous cooling over the entire bus ring surface is not possible and the individual filaments exhibit a higher dispersion in their mechanical properties. The aim of the GLASSCOOLER project is to develop a new system component for active cooling of the individual filaments and the necessary measurement and control units. By optically measuring all fibers during solidification and adaptively controlling the cooling, it is possible to reduce the variation in mechanical properties across all filaments and thus achieve higher overall strength. In addition, documentation of fiber properties during the manufacturing process is enabled and quality checks are automated.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Textile Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; OTOMASYON & KONTROL SİSTEMLERİ; TELEKOMÜNİKASYON; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; AUTOMATION & CONTROL SYSTEMS; TELECOMMUNICATIONS; MATERIALS SCIENCE, TEXTILES; Kontrol ve Optimizasyon; Bilgisayar Ağları ve İletişim; Fizik Bilimleri; Control and Optimization; Control and Systems Engineering; Computer Networks and Communications; Physical Sciences